Metabolic risk factors of cognitive impairment in young women with major psychiatric disorder - Zhuo, Chuanjun; Liu, Wei; Jiang, Ronghuan; Li, Ranli; Yu, Haiping; Chen, Guangdong; Shan, Jianmin; Zhu, Jingjing; Cai, Ziyao; Lin, Chongguang; Cheng, Langlang; Xu, Yong; et al. (Frontiers in Psychiatry, 2022)
Background: Cognitive performance improves clinical outcomes of patients with major psychiatric disorder (MPD), but is impaired by hyperglycemia. Psychotropic agents often induce metabolism syndrome (MetS). Biomarkers of MetS and cognitive impairment risk are urgently needed. Objective: To investigate the relationship between MetS and cognitive impairment in young women with MPD, and to explore risk factors. Methods: We retrospectively studied women of 18–34 years of age receiving psychotropic medications for first-onset schizophrenia (SCH), bipolar disorder (BP), or major depressive disorder (MDD). Data were obtained at four time points: presentation but before psychotropic medication; 4–8 weeks and 8–12 weeks of psychotropic therapy; and enrollment. MATRICS Consensus Cognitive Battery, (MCCB) –based Global Deficit Scores were used to assess cognitive impairment. Multiple logistic analysis was used to calculate risk factors. Multivariate models were used to investigate factors associated with cognitive impairment. Results: We evaluated 2864 participants. Cognitive impairment was observed in 61.94%. and was most prevalent in BP (69.38%). HbA1c within the 8–12 week-treatment interval was the most significant risk factor and highest in BP. Factors in SCH included pre-treatment waist circumference and elevated triglycerides during the 8–12 weeks treatment interval. Cumulative dosages of antipsychotics, antidepressants, and valproate were associated with cognitive impairment in all MPD subgroups, although lithium demonstrated a protect effect (all P<0.001). Conclusions: Cognitive impairment was associated with elevated HbA1c and cumulative medication dosages. Pre-treatment waist circumference and triglyceride level at 8–12 weeks were risk factors in SCH. Monitoring these indices may inform treatment revisions to improve clinical outcomes.